Erotic Transgression and The Allure of Innocent Woman: Analysis on Hijab Pornography in a Muslim-majority Country - Umam, Ahmad Naufalul; Istiqomah, Istiqomah (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2025)
There is a sub-culture of hijab erotica in a country where hijab used to be a symbol of rebellion against the oppressive regime and became a conservative norm in a conservative-leaning society that rejects pornography. Researcher gathered erotic stories from an internet forum involving the characters of hijabi women as the main character. Through thematic analysis, researcher found several key themes in the stories. The themes are the identity of hijabi women as both familiar and exotic, the erotic transgression in sexual acts, the allure of innocent women, and hijab as a significant accessory in sexual intercourse. The result of this research strengthens the notion of pornography as an everchanging historical record that caught the nuance of how people view sex and its expression in any particular era of interest.